2017
DOI: 10.3171/2016.6.spine1656
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with venous thromboembolism in patients undergoing spine surgery

Abstract: OBJECTIVE Patients undergoing spinal surgery are at risk for developing venous thromboembolism (VTE). The authors sought to identify risk factors for VTE in these patients. METHODS The American College of Surgeons National Surgical Quality Improvement Project database for the years 2006–2010 was reviewed for patients who had undergone spinal surgery according to their primary Current Procedural Terminolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 46 publications
3
38
1
3
Order By: Relevance
“…78,[82][83][84][85] In contrast, the increased risk of VTE due to prolonged operative duration has been linked to factors such as increased coagulation, blood stasis, and endothelial damage resulting from longer surgical procedures. [86][87][88][89] Prolonged operative times are also associated with increased surgical team fatigue and extension of anesthesia durationdfactors that enhance the risk for many different types of complications. [90][91][92] However, it is also plausible that complications can, in reverse, prolong the duration of surgical procedures and hence contribute to the positive association between operative duration and complication risk.…”
Section: Discussionmentioning
confidence: 99%
“…78,[82][83][84][85] In contrast, the increased risk of VTE due to prolonged operative duration has been linked to factors such as increased coagulation, blood stasis, and endothelial damage resulting from longer surgical procedures. [86][87][88][89] Prolonged operative times are also associated with increased surgical team fatigue and extension of anesthesia durationdfactors that enhance the risk for many different types of complications. [90][91][92] However, it is also plausible that complications can, in reverse, prolong the duration of surgical procedures and hence contribute to the positive association between operative duration and complication risk.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have endeavored to use national databases to characterize incidence and risk factors for VTE in large, nationally representative samples [13][14][15][16]. The American College of Surgeons' National Surgical Quality Improvement Program (NSQIP) is a national database consisting of more than 600 hospitals that catalog demographic, comorbidity, intraoperative, and postoperative factors up to Postoperative Day 30 for various surgical procedures [17].…”
Section: Introductionmentioning
confidence: 99%
“…Past investigations have characterized risk factors for VTE in the NSQIP sample [15,16]. However, by including patients with high-risk profiles (eg, trauma and emergency cases), these studies may not accurately describe patients undergoing elective surgery who may have a different risk profile.…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis by Piper et al revealed 13 factors associated with VTE: nine preoperative factors (dependent functional status, paraplegia, quadriplegia, disseminated cancer, inpatient status, hypertension, history of transient ischemic attack, sepsis, and African American race); three operative factors (surgery duration >4 hours, emergency presentation, and American Society of Anesthesiologists Class III‐V); and one postoperative factor, sepsis . Another meta‐analysis describing VTE incidence showed higher incidence of VTE after spine surgery when wearing elastic stockings, undergoing lumbar surgery, having a history of hypertension and diabetes, being of Asian descent, or having ambulatory impairments prior to surgery .…”
Section: Discussionmentioning
confidence: 99%